علاج ونتائج أذيات الصدر الحربية - رومية دمر (Latakia University Journal -Medical Sciences Series, 2018)
The main aim of our study is to analyze the different therapeutical procedures in the war chest injuries and its results as well. Medical Files of (542) casualties sustaining war chest injuries were analyzed during the study period. The majority of the injured patients were young males. 73.06% of the casualties were treated with a simple procedure including the insertion of chest drains only, whereas the remaining 26.9% underwent thoracotomies ; 53.42% of these sustained lung lacerations, which treated surgically by means of sparing surgery in form of atypical segment resection, suturing of the lung parenchyma and tractotomy as well ; the results were encouraging. only 7.53 % were treated by lobectomies, the indications for these were injuries to the lobar bronchus or vessels. Decortications were performed in 23.97% of the patients as results of neglected or residual hemothorax and thoracic empyema. Hospital stay was 6 days in case of chest tube insertion , 13 days when performing thoracotomy. Hospital stay was greatly increased ( until 37 days ) in case of associated extra thoracic injuries. Total mortality rate was 6.27%. this rate was 3.29% when performing thoracotomy, whereas it increased 7-8 folds in combined thoracic and extra thoracic procedures. Cerebral injuries were the leading cause of Death in our patients and were responsible for 55.8% of the mortality rate. إنَّ الهدف الرئيس من هذه الدراسة هو تحليل الطرق العلاجية المختلفة للإصابات الصدرية الحربية ودراسة نتائجها. تمت دراسة الملفات الطبية لـ (542) مريضاً مصاباً بأذية صدر حربية أثناء فترة البحث. كان أغلب المرضى من الشباب الذكور. 73.06% من المرضى المصابين برضوض صدر حربية تمت معالجتهم بإجراء جراحي بسيط تمثل بوضع مفجر صدر، أما النسبة المتبقية وهي 26.9% فقد أجري لهم فتح صدر، 53.42% من هؤلاء حصلت لديهم تمزقات رئة، طبقت على هؤلاء المرضى الجراحة الإدخارية على شكل استئصال قسمي لا نموذجي، خياطة البرانشيم الرئوي وكذلك خزع السبيل وكانت النتائج جيدة باستخدام هذه الطرق. 7.53% من المرضى أجريت لهم استئصالات فصية بسبب أذية أوعية وقصبة الفصوص. تقشير الجنب والرئة أجري في 23.97% من الجرحى بسبب تدّمي جنب مهمل أو متبقي وكذلك بسبب حدوث دبيلة صدرية. اختلفت مدة بقاء المرضى في المشفى حسب الاصابة وطريقة العلاج حيث بلغت (6) أيام في حالة تفجير الصدر و (13) يوماً في حالات فتح الصدر، ازدادت هذه المدة حتى (37) يوماً عند ترافق الأذيات الصدرية مع أذيات أخرى خارج الصدر. بلغت نسبة الوفيات الاجمالية %6.27 ، هذه النسبة كانت 3.29% لدى مرضى فتح الصدر، وتضاعفت حوالي (7-8) مرات عندما يترافق الاجراء الجراحي الصدري مع اجراءات أخرى خارج الصدر، وكانت الاصابات الدماغية مسؤولة عن 55.8% من وفيات مرضانا.